The Eight International Mycorrhiza Conference (IC0M8) Northern Arizona University, Flagstaff, USA - Chan, Margaret Kit Yok (UiTM Sarawak, 2016)
The Eight International Mycorrhiza Conference (ICOM8) was held in Northern Arizona University in Flagstaff, Arizona, USA from 2nd to 9* August 2015. My participation was partially sponsored by the Sarawak Convention Bureau to bid for the ninth session to be held in Kuching, Sarawak, but was not successful as the delegates voted Prague, Czechoslovakia over Kuching, Sarawak and Morocco. I was also accepted to present a poster paper entitled, "Land use change in tropical peat on vesicular arbuscular mycorrhiza of sago palm (Metroxylon sagu rottboll)". Indeed, it was like a reunion for me as I was able to meet other delegates whom I crossed paths at previous conferences on mycorrhizas and updated our research experiences and findings.